August Cieszkowski o Indiach. Uwagi na marginesie Ojcze Nasz - Sajdek, Paweł. (Gajt Wydawnictwo 1991 s.c., 2018)
The reception of Indian culture in 19th c. was not free from stereotyping. The present discussion is focused on three views of August Cieszkowski (1814–1894) expressed in his Our Father (Ojcze nasz). The views concern Indian philosophy, politics and religion – the alleged Indian pantheism, oriental despotism and Buddhism as Indian Gospel respectively. The early stage of research on indology may justify Cieszkowski’s erroneous views. The true problem is their striking resemblance to the stereotypes of our times, in spite of the availibility of knowledge in books and Internet.
Keywords: August Cieszkowski